2009
DOI: 10.1111/j.1365-2699.2008.02046.x
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of core and occasional species in the marine plankton: tintinnid ciliates in the north‐west Mediterranean Sea

Abstract: Aim To assess short-term variability in the community composition and community structure of tintinnid ciliates, herbivores of the microzooplankton.Location North-west Mediterranean Sea.Methods We sampled on 18 dates over a 4-week period in 2004 at an openwater site. Species were classified as 'core species', found on every date, or 'occasional species', absent on one or more dates. Species abundance distributions of the entire community, and separately the core and occasional species, were compared with geome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
78
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(83 citation statements)
references
References 30 publications
3
78
0
1
Order By: Relevance
“…This would indicate that skewed observations of local community composition are reached without prior PMA treatment. The effects of PMA treatment at the metacommunity level At the metacommunity level, it has been established that a dichotomy exists within metacommunity species abundance distributions (SADs), consisting of 'regionally' common and locally abundant core species and infrequent rare satellite species groups (for example, Magurran and Henderson, 2003;Ulrich and Zalewski, 2006;Dolan et al, 2009;Unterseher et al, 2011). Recently, we established that the core-satellite group approach can be applied to CF bacterial communities and that partitioning the two groups from a metacommunity revealed important aspects of SADs, which would otherwise be neglected without such a distinction (van der Gast et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…This would indicate that skewed observations of local community composition are reached without prior PMA treatment. The effects of PMA treatment at the metacommunity level At the metacommunity level, it has been established that a dichotomy exists within metacommunity species abundance distributions (SADs), consisting of 'regionally' common and locally abundant core species and infrequent rare satellite species groups (for example, Magurran and Henderson, 2003;Ulrich and Zalewski, 2006;Dolan et al, 2009;Unterseher et al, 2011). Recently, we established that the core-satellite group approach can be applied to CF bacterial communities and that partitioning the two groups from a metacommunity revealed important aspects of SADs, which would otherwise be neglected without such a distinction (van der Gast et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Even if water mixing is expected to transport species across the shelf, environmental selection could prevent establishment (growth) when conditions are non-optimal, and thus limit the successful dispersal (colonization) in the new environment. An additional or alternative process operating on the shelf may be drift (for example, random dispersal), especially in determining the distribution of ecologically similar species within inshore, offshore and deep waters (Dolan et al, 2007(Dolan et al, , 2009). …”
Section: Ecological Processes Linked To Spatial Patternsmentioning
confidence: 99%
“…Indeed, assemblages of tintinnid morphospecies differ markedly in the bathymetric, latitudinal and vertical profiles (for example, Alder, 1999;Modigh et al, 2003;Santoferrara and Alder, 2012), as well as in the seasonal cycle of temperate coasts (for example, Bojanić et al, 2012). Structuring of morphospecies assemblages has been explained by environmental selection in a coastal site (Sitran et al, 2009) or random dispersal in open waters (Dolan et al, 2007(Dolan et al, , 2009(Dolan et al, , 2013b, but the processes that affect assembly in the transitions between environments are unknown. Likewise, it is not known whether patterns and processes based on morphologies and molecules agree, as few distribution studies have used DNA sequences to target tintinnids and aloricate sister lineages (Doherty et al, 2010;Tamura et al, 2011;Bachy et al, 2014;Grattepanche et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Recalling the patterns found among diatoms and dinoflagellates (Lasternas et al, 2008), the number of species found on each sampling date varied within a narrow range while the identity of the taxa changed (Dolan et al, 2009). However, the identity of the most common "core" species, representing a small part of the species lists but accounting for the overwhelming majority of individuals, was invariant, a pattern also described for the large (>500 µm) copepods (Raybaud et al, 2008b).…”
Section: Andersen Et Al: Short-scale Temporal Variability In the mentioning
confidence: 99%